How Sustainable Mutual Funds Have Performed against Financial Markets : Evidence from the Equity Mutual Funds in the United States - Paussoi, Iida (My University, 2025)
The popularity of sustainability and socially responsible investing has gained considerable market attention in recent years. However, both theories and previous research have conflicting findings on the profitability of the trend. Depending on the study, the performance of ESG funds results in negative, neutral, or positive returns. Therefore, this thesis hypothesizes that ESG implementation has a neutral effect on mutual fund performance on a risk-adjusted basis. The sample for this study consists of 150 equity funds in the United States. The funds are divided into three portfolios based on their sustainability, and all the formed portfolios are comprised of 50 equity mutual funds. This thesis investigates how sustainable funds have performed against their conventional counterparts. Sustainability ratings for the thesis are collected from the MSCI website. Monthly returns are collected for the period 2015-2024. The study uses the Capital Asset Pricing model, Fama and French's three-, five-, and six-factor models. The results of this thesis indicate that incorporating ESG into mutual fund selection results in lower returns. All three formed portfolios lost risk-adjusted return for the selected S&P 500 benchmark index. All the portfolios have statistically significant negative alphas and insignificant relative differences. The average portfolio produced the highest return from the formed portfolios, which supports the hypothesis that ESG results in neutral performance. Conventional funds have been found to have lower fees, which increases their popularity among investors. However, incorporating ESG into an investor’s portfolio can lower volatility and risk level, and some investors are ready to accept lower returns.

Kestävän kehityksen ja sosiaalisesti vastuullisen sijoittamisen suosio on saanut viime vuosina markkinoilla paljon huomiota. Sekä teorioilla että aikaisemmilla tutkimuksilla on kuitenkin ristiriitaisia tuloksia koskien trendin kannattavuutta. Riippuen tutkimuksesta, ESG-rahastot voivat näyttäytyä negatiivisena, neutraalina tai positiivisena tuottona. Tämän opinnäytetyön hypoteesi on, että ESG:n käyttöönotolla on neutraali vaikutus sijoitusrahastojen riskikorjattuun tuottoon. Tämän tutkimuksen otos sisältää 150 osakerahastoa Yhdysvalloissa. Rahastot on jaettu kolmeen salkkuun niiden kestävyyden perusteella, ja kaikki muodostuvat salkut sisältävät 50 osakerahastoa. Tässä opinnäytetyössä tarkastellaan, kuinka vastuulliset rahastot ovat pärjänneet perinteisiä rahastoja vastaan. Opinnäytetyön kestävän kehityksen luokitukset on kerätty MSCI:n verkkosivuilta. Kuukausittaiset tuotot on kerätty aikaväliltä 2015–2024. Tutkimuksessa käytetään Capital Asset Pricing -mallia sekä Faman ja Frenchin kolmi-, viisi- ja kuusifaktorimalleja. Tämän opinnäytetyön tulokset osoittavat, että ESG:n sisällyttäminen sijoitusrahastojen valintaan johtaa pienempään tuottoon. Kaikki kolme muodostettua salkkua menettivät riskikorjatun tuoton valitulle S&P 500 vertailuindeksille. Kaikissa salkuissa on tilastollisesti merkitseviä negatiivisia alfa-arvoja ja merkityksettömiä suhteellisia eroja. Keskimääräinen salkku tuotti korkeimman tuoton muodostetuista salkuista, mikä tukee olettamusta, että ESG johtaa neutraaliin tulokseen. Perinteisissä rahastoissa on havaittu alhaisemmat palkkiot, mikä lisää niiden suosiota sijoittajien keskuudessa. ESG:n sisällyttäminen sijoittajan salkussa voi kuitenkin vähentää volatiliteettia ja riskiä, ja jotkut sijoittajat ovat valmiita hyväksymään alhaisemman tuoton.
Keywords: mutual funds; corporate responsibility; responsible investing; societal responsibility; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance